Mobile Application for Vocational Job Vacancies Innovation: Applying Creative Critical Canvas - Wahyu Ridhoni; Yazid Aufar; Emma Valensia Aurum (CV. Edutechnium Indonesia, 2025)
This research aims to improve the connection between vocational universities and industries in South Kalimantan through the development of a job vacancy test platform. By applying the concept of “link and match”, this research identifies the needs of vocational universities and industry. The method used is Creative Critical Canvas, which includes six stages: parse, deviate, modify, verify, compare, and conclude. The results showed that current job vacancy announcements still face problems in terms of information dissemination and complicated application procedures. The innovative solution in the form of an automation system and user experience validation was successfully tested by involving 66 respondents, resulting in validation scores that showed a good interface but required minor revisions at the ease of use and user friendly before continuing development at the coding stage. This research also concluded that Creative Critical Canvas is effective as a framework in creating innovation and can be used for digital product development.